A formação tecnológica do professor de Inglês e o uso de tecnologias digitais de informação e comunicação - Luz, Carla Cíntia (2019)
This research aims at describing and interpreting the experience lived by teachers of English who in the city of São Paulo use technological resources in their classes, understood as a phenomenon of lived experience. Theoretically this research is grounded on the Complexity Epistemology (MORIN, 2000, 2003, 2005, 2006, 2012, 2015a, 2015b), on the teachers technological self-heteroecoformation (FREIRE, 2009; FREIRE; LEFFA, 2013), and on aspects that refer to the information and communication digital tools (ALMEIDA; VALENTE, 2011; KENSKI, 2003; 2012; LEFFA; ARAÚJO, 2016). Methodologically this research is based on the complex hermeneutic-phenomenological approach (FREIRE, 2010, 2012, 2017), and is focused on the following research question: What’s the nature of the experience lived by teachers of English who use technological resourses in their classes? Five teachers participate in this reseach: one who works in a language institute, one who teaches in a private school, and three who work in public schools. The research began with the production of a professional narrative that provided details about the participants’ professional life, according to their own view. The second instrument used was a narrative of the participants’ technological education. The third instrument was the answer to a question that was focused on the participants’ opinion about their own experience in using technological resources in their classes. All the instruments and eventual clarification on them were conveyed through the electronic medium (e-mail and Whatsapp). The interpretation of the texts produced by the participants reveals that advantage, necessity and problem are the constructs that constitute the essence of the phenomenon on focus. The research outcomes also provide subsidies to plan and design teacher education courses at undergraduate, graduate, and extension levels - courses that may reach the needs and expectations of teachers as a whole